Healthy snack quartet education on knowledge and sodium intake in overweight early adolescents - Sapang, Ferliani Fransisca; Andayani, Tri Rejeki; Muthmainah, Muthmainah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Child and adolescent obesity cases are estimated to reach 49.5 million cases worldwide by 2030. Nutrition education interventions to increase knowledge about healthy snacks in adolescents are important as a form of obesity prevention in adolescents. Healthy snacks quartet is an educational media that is carried out with a group game method so that adolescents feel comfortable in the learning process.Objective: To determine the effect of healthy snacks quartet education on knowledge and sodium intake in overweight early adolescents. Methods: This study is a quasi-experimental study with pre-posttest with control group design. The sample was purposively selected and 54 overweight adolescents were divided into a control group and two intervention groups. Education using healthy snacks quartet was conducted for 21 days from September to October 2023 in Makassar City. Data analysis was performed using Wilcoxon singed ranks test. Results: There was a significant difference in adolescent knowledge with a p-value <0.05 in P1 (p=0.001) and P2 (p=0.000). However, there was no significant difference in sodium intake variables both in the control group (p=0.948), P1 (p=0.170) and P2 (p=0.170).Conclusion: Education using healthy snacks quartet can increase knowledge about healthy snacks in overweight early adolescents but does not have a significant impact on sodium intake of overweight adolescents. KEYWORDS: Natrium Intake; Nutrition Education; Knowledge; Overweight Adolescent